Heteroclinic dynamics in network dynamical systems with higher-order interactions - Bick, Christian; von der Gracht, Sören (Journal of Complex Networks)
Heteroclinic structures organize global features of dynamical systems. We analyse whether heteroclinic structures can arise in network dynamics with higher-order interactions which describe the nonlinear interactions between three or more units. We find that while commonly analysed model equations such as network dynamics on undirected hypergraphs may be useful to describe local dynamics such as cluster synchronization, they give rise to obstructions that allow to design of heteroclinic structures in phase space. By contrast, directed hypergraphs break the homogeneity and lead to vector fields that support heteroclinic structures.
Keywords: Applied Mathematics; Computational Mathematics; Control and Optimization; Management Science and Operations Research; Computer Networks and Communications

TS-SEP: Joint Diarization and Separation Conditioned on Estimated Speaker Embeddings - Boeddeker, Christoph; Subramanian, Aswin Shanmugam; Wichern, Gordon; Haeb-Umbach, Reinhold; Le Roux, Jonathan (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Keywords: Electrical and Electronic Engineering; Acoustics and Ultrasonics; Computer Science (miscellaneous); Computational Mathematics

The Stellarium Gornergrat: Astrophysics with your own Data - Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Nordine, Jeffrey; Riesen, Timm-Emanuel (Journal of Physics: Conference Series)
Abstract Remote-controlled telescopes in education provide the opportunity to obtain high quality astronomy images for a broad variety of users. The Stellarium Gornergrat is such a telescope. In addition to pure observation, it offers a user-friendly interface and teaching modules so that astronomical and astrophysical projects can be integrated into everyday school life without any special prior knowledge and without requiring a lot of time. This contribution presents the Stellarium project and a provides an overview of several teaching activities.
Keywords: Computer Science Applications; History; Education

An Integrated Fuzzy Analytic Network Process and Fuzzy Regression Method for Bitcoin Price Prediction - Amiri, Arman; Tavana, Madjid; Arman, Hosein (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Empowering Students for the Data-Driven World: A Qualitative Study of the Relevance of Learning about Data-Driven Technologies - Höper, Lukas; Schulte, Carsten (Informatics in Education)
In K-12 computing education, there is a need to identify and teach concepts that are relevant to understanding machine learning technologies. Studies of teaching approaches often evaluate whether students have learned the concepts. However, scant research has examined whether such concepts support understanding digital artefacts from everyday life and developing agency in a digital world. This paper presents a qualitative study that explores students’ perspectives on the relevance of learning concepts of data-driven technologies for navigating the digital world. The underlying approach of the study is data awareness, which aims to support students in understanding and reflecting on such technologies to develop agency in a data-driven world. This approach teaches students an explanatory model encompassing several concepts of the role of data in data-driven technologies. We developed an intervention and conducted retrospective interviews with students. Findings from the analysis of the interviews indicate that students can analyse and understand data-driven technologies from their everyday lives according to the central role of data. In addition, students’ answers revealed four areas of how learning about data-driven technologies becomes relevant to them. The paper concludes with a preliminary model suggesting how computing education can make concepts of data-driven technologies meaningful for students to understand and navigate the digital world.
Keywords: Computer Science Applications; Communication; Education; General Engineering

Evaluating Security Through Isolation and Defense in Depth - Bodden, Eric; Pottebaum, Jens; Fockel, Markus; Gräßler, Iris (IEEE Security & Privacy)
Keywords: Law; Electrical and Electronic Engineering; Computer Networks and Communications

Gathering a Euclidean Closed Chain of Robots in Linear Time and Improved Algorithms for Chain-Formation - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Knollmann, Till; Meyer auf der Heide, Friedhelm (Theoretical Computer Science)
Keywords: General Computer Science; Theoretical Computer Science

Realization of a Multi-Output Quantum Pulse Gate for Decoding High-Dimensional Temporal Modes of Single-Photon States - Serino, Laura; Gil López, Jano; Stefszky, Michael; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
Keywords: General Physics and Astronomy; Mathematical Physics; Applied Mathematics; Electronic; Optical and Magnetic Materials; Electrical and Electronic Engineering; General Computer Science

Methodology for Certification-Compliant Effect-Chain Modeling - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Sturm, Tim; Markfelder, Thomas (Systems)
The success of engineering complex technical systems is determined by meeting customer requirements and institutional regulations. One example relevant to the automobile industry is the United Nations Economic Commission of Europe (UN ECE), which specifies the homologation of automobile series and requires proof of traceability. The required traceability can be achieved by modeling system artifacts and their relations in a consistent, seamless model—an effect-chain model. Currently, no in-depth methodology exists to support engineers in developing certification-compliant effect-chain models. For this purpose, a new methodology for certification-compliant effect-chain modeling was developed, which includes extensions of an existing method, suitable models, and tools to support engineers in the modeling process. For evaluation purposes, applicability is proven based on the experience of more than 300 workshops at an automotive OEM and an automotive supplier. The following case example is chosen to demonstrate applicability: the development of a window lifter that has to meet the demands of UN ECE Regulations R156 and R21. Results indicate multiple benefits in supporting engineers with the certification-compliant modeling of effect chains. Three benefits are goal-oriented modeling to reduce the necessary modeling capacity, increasing model quality by applying information quality criteria, and the potential to reduce costs through automatable effect-chain analyses for technical changes. Further, companies in the automotive and other industries will benefit from increased modeling capabilities that can be used for architecture modeling and to comply with other regulations such as ASPICE or ISO 26262.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

Algorithms for the genome median under a restricted measure of rearrangement - Silva, Helmuth O.M.; Rubert, Diego P.; Araujo, Eloi; Steffen, Eckhard; Doerr, Daniel; Martinez, Fábio V. (RAIRO - Operations Research)
Ancestral reconstruction is a classic task in comparative genomics. Here, we study the genome median problem, a related computational problem which, given a set of three or more genomes, asks to find a new genome that minimizes the sum of pairwise distances between it and the given genomes. The distance stands for the amount of evolution observed at the genome level, for which we determine the minimum number of rearrangement operations necessary to transform one genome into the other. For almost all rearrangement operations the median problem is NP-hard, with the exception of the breakpoint median that can be constructed efficiently for multichromosomal circular and mixed genomes. In this work, we study the median problem under a restricted rearrangement measure called c4-distance, which is closely related to the breakpoint and the DCJ distance. We identify tight bounds and decomposers of the c4-median and develop algorithms for its construction, one exact ILP-based and three combinatorial heuristics. Subsequently, we perform experiments on simulated data sets. Our results suggest that the c4-distance is useful for the study the genome median problem, from theoretical and practical perspectives.
Keywords: Management Science and Operations Research; Computer Science Applications; Theoretical Computer Science

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed Ahmed; da Silva, Ana Alexandra Morim; Pestryakova, Svetlana; Ahmed, Abdullah Fathi; Niemann, Sven; Ngomo, Axel-Cyrille Ngonga (Scientific Data)
Abstract Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project ( Ingrid ) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid , the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present Ingrid KG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update Ingrid KG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of Ingrid KG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.
Keywords: Library and Information Sciences; Statistics; Probability and Uncertainty; Computer Science Applications; Education; Information Systems; Statistics and Probability

Multi-FPGA Designs and Scaling of HPC Challenge Benchmarks via MPI and Circuit-Switched Inter-FPGA Networks - Meyer, Marius; Kenter, Tobias; Plessl, Christian (ACM Transactions on Reconfigurable Technology and Systems)
While FPGA accelerator boards and their respective high-level design tools are maturing, there is still a lack of multi-FPGA applications, libraries, and not least, benchmarks and reference implementations towards sustained HPC usage of these devices. As in the early days of GPUs in HPC, for workloads that can reasonably be decoupled into loosely coupled working sets, multi-accelerator support can be achieved by using standard communication interfaces like MPI on the host side. However, for performance and productivity, some applications can profit from a tighter coupling of the accelerators. FPGAs offer unique opportunities here when extending the dataflow characteristics to their communication interfaces. In this work, we extend the HPCC FPGA benchmark suite by multi-FPGA support and three missing benchmarks that particularly characterize or stress inter-device communication: b_eff, PTRANS, and LINPACK. With all benchmarks implemented for current boards with Intel and Xilinx FPGAs, we established a baseline for multi-FPGA performance. Additionally, for the communication-centric benchmarks, we explored the potential of direct FPGA-to-FPGA communication with a circuit-switched inter-FPGA network that is currently only available for one of the boards. The evaluation with parallel execution on up to 26 FPGA boards makes use of one of the largest academic FPGA installations.
Keywords: General Computer Science

Steady-State Error Compensation for Reinforcement Learning-Based Control of Power Electronic Systems - Weber, Daniel; Schenke, Maximilian; Wallscheid, Oliver (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Breaking the exascale barrier for the electronic structure problem in ab-initio molecular dynamics - Schade, Robert; Kenter, Tobias; Elgabarty, Hossam; Lass, Michael; Kühne, Thomas; Plessl, Christian (The International Journal of High Performance Computing Applications)
The non-orthogonal local submatrix method applied to electronic structure–based molecular dynamics simulations is shown to exceed 1.1 EFLOP/s in FP16/FP32-mixed floating-point arithmetic when using 4400 NVIDIA A100 GPUs of the Perlmutter system. This is enabled by a modification of the original method that pushes the sustained fraction of the peak performance to about 80%. Example calculations are performed for SARS-CoV-2 spike proteins with up to 83 million atoms.
Keywords: Hardware and Architecture; Theoretical Computer Science; Software

NELLIE: Never-Ending Linking for Linked Open Data - Ahmed, Abdullah Fathi; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Adsorption of Ferritin at Nanofaceted Al2O3 Surfaces - Pothineni, Bhanu K.; Kollmann, Sabrina; Li, Xinyang; Grundmeier, Guido; Erb, Denise J.; Keller, Adrian (International Journal of Molecular Sciences)
The influence of nanoscale surface topography on protein adsorption is highly important for numerous applications in medicine and technology. Herein, ferritin adsorption at flat and nanofaceted, single-crystalline Al2O3 surfaces is investigated using atomic force microscopy and X-ray photoelectron spectroscopy. The nanofaceted surfaces are generated by the thermal annealing of Al2O3 wafers at temperatures above 1000 °C, which leads to the formation of faceted saw-tooth-like surface topographies with periodicities of about 160 nm and amplitudes of about 15 nm. Ferritin adsorption at these nanofaceted surfaces is notably suppressed compared to the flat surface at a concentration of 10 mg/mL, which is attributed to lower adsorption affinities of the newly formed facets. Consequently, adsorption is restricted mostly to the pattern grooves, where the proteins can maximize their contact area with the surface. However, this effect depends on the protein concentration, with an inverse trend being observed at 30 mg/mL. Furthermore, different ferritin adsorption behavior is observed at topographically similar nanofacet patterns fabricated at different annealing temperatures and attributed to different step and kink densities. These results demonstrate that while protein adsorption at solid surfaces can be notably affected by nanofacet patterns, fine-tuning protein adsorption in this way requires the precise control of facet properties.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

The potential of digital nudging to bridge the gap between environmental attitude and behavior in the usage of smart home applications - Stieglitz, Stefan; Mirbabaie, Milad; Deubel, Annika; Braun, Lea-Marie; Kissmer, Tobias (International Journal of Information Management)
Keywords: Library and Information Sciences; Computer Networks and Communications; Information Systems

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David (Computers & Education)
Keywords: Education; General Computer Science

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David (Computers & Education)
Keywords: Education; General Computer Science

ARIadne – An Explanation Model for Digital Artefacts - Winkelnkemper, Felix; Höper, Lukas; Schulte, Carsten (Informatics in Education)
When it comes to mastering the digital world, the education system is more and more facing the task of making students competent and self-determined agents when interacting with digital artefacts. This task often falls to computing education. In the traditional fields of computing education, a plethora of models, guidelines, and principles exist, which help scholars and teachers identify what the relevant aspects are and which of them one should cover in the classroom. When it comes to explaining the world of digital artefacts, however, there is hardly any such guiding model. The ARIadne model introduced in this paper provides a means of explanation and exploration of digital artefacts which help teachers and students to do a subject analysis of digital artefacts by scrutinizing them from several perspectives. Instead of artificially separating aspects which target the same phenomena within different areas of education (like computing, ICT or media education), the model integrates technological aspects of digital artefacts and the relevant societal discourses of their usage, their impacts and the reasons behind their development into a coherent explanation model.
Keywords: Computer Science Applications; Communication; Education; General Engineering

Echtzeitfähige Modellierung eines innovativen Drückwalzprozesses für die eigenschaftsgeregelte Bauteilfertigung - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (at - Automatisierungstechnik)
Zusammenfassung Aufgrund aktueller Transformationsprozesse kommt der automatisierten und ressourceneffizienten Fertigung hochfester Leichtbauteile eine steigende Bedeutung zu, beispielsweise im Flugzeug- und Fahrzeugbau. Für kleine Losgrößen bietet sich hier insbesondere das Fertigungsverfahren des Drückwalzens an. Der konventionelle, industriell genutzte Drückwalzprozess stößt allerdings aufgrund der Prozesskomplexität hinsichtlich der Reproduzierbarkeit an seine Grenzen. Dies wird in der Praxis teilweise durch personengebundenes Erfahrungswissen kompensiert. Auch ist es nicht möglich, Bauteileigenschaften definiert einzustellen. Aus diesem Grund bietet der Einsatz einer neuartigen Eigenschaftsregelung Chancen zur Weiterentwicklung des Fertigungsprozesses und die Möglichkeit zur Prozessautomatisierung. Hier werden die Werkzeugbahnen abhängig einer Online-Eigenschaftsmessung über eine zusätzliche Reglerkaskade manipuliert. Die Entwicklung einer solchen Eigenschaftsregelung erfordert den Einsatz geeigneter, modellbasierter Entwurfsmethoden. In diesem Beitrag wird daher ein regelungstechnisches Systemmodell für das Drückwalzen metastabiler austenitischer Edelstähle vorgestellt. Das Simulationsmodell weist aufgrund seiner Echtzeitfähigkeit neben dem Einsatz als reines Entwurfsmodell weitere Nutzungsmöglichkeiten z.B. in Beobachtern auf und grenzt sich somit von domänenspezifischen Simulationstools wie der FEM ab.
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Lessons Learned from the Introduction of Systems Engineering - Wilke, Daria; Grothe, Robin; Bretz, Lukas; Anacker, Harald; Dumitrescu, Roman (Systems)
The introduction of Systems Engineering is an approach for dealing with the increasing complexity of products and their associated product development. Several introduction strategies are available in the literature; nevertheless, the introduction of Systems Engineering into practice still poses a great challenge to companies. Many companies have already gained experience in the introduction of Systems Engineering. Therefore, as part of the SE4OWL research project, the need to conduct a study including expert interviews and to collect the experiences of experts was identified. A total of 78 hypotheses were identified from 13 expert interviews concerning the lessons learned. Using exclusion criteria, 52 hypotheses were validated in a subsequent quantitative survey with 112 participants. Of these 52 hypotheses, 40 could be confirmed based on the survey results. Only four hypotheses were rejected, and eight could neither be confirmed nor rejected. Through this research, guidance is provided to companies to leverage best practices for the introduction of their own Systems Engineering and to avoid the poor practices of other companies.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

Performance and Usability Evaluation of Brainwave Authentication Techniques with Consumer Devices - Arias-Cabarcos, Patricia; Fallahi, Matin; Habrich, Thilo; Schulze, Karen; Becker, Christian; Strufe, Thorsten (ACM Transactions on Privacy and Security)
Brainwaves have demonstrated to be unique enough across individuals to be useful as biometrics. They also provide promising advantages over traditional means of authentication, such as resistance to external observability, revocability, and intrinsic liveness detection. However, most of the research so far has been conducted with expensive, bulky, medical-grade helmets, which offer limited applicability for everyday usage. With the aim to bring brainwave authentication and its benefits closer to real world deployment, we investigate brain biometrics with consumer devices. We conduct a comprehensive measurement experiment and user study that compare five authentication tasks on a user sample up to 10 times larger than those from previous studies, introducing three novel techniques based on cognitive semantic processing. Furthermore, we apply our analysis on high-quality open brainwave data obtained with a medical-grade headset, to assess the differences. We investigate both the performance, security, and usability of the different options and use this evidence to elicit design and research recommendations. Our results show that it is possible to achieve Equal Error Rates as low as 7.2% (a reduction between 68–72% with respect to existing approaches) based on brain responses to images with current inexpensive technology. We show that the common practice of testing authentication systems only with known attacker data is unrealistic and may lead to overly optimistic evaluations. With regard to adoption, users call for simpler devices, faster authentication, and better privacy.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Multiphase elasto-plastic mean-field homogenisation and its consistent linearisation - Lenz, Peter; Kreutzheide, Phil; Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

“I do not know! but why?” — Local model-agnostic example-based explanations of reject - Artelt, André; Visser, Roel; Hammer, Barbara (Neurocomputing)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

RISE: an open-source architecture for interdisciplinary and reproducible human–robot interaction research - Groß, André; Schütze, Christian; Brandt, Mara; Wrede, Britta; Richter, Birte (Frontiers in Robotics and AI)
In this article, we present RISE—a R obotics I ntegration and S cenario-Management E xtensible-Architecture—for designing human–robot dialogs and conducting Human–Robot Interaction (HRI) studies. In current HRI research, interdisciplinarity in the creation and implementation of interaction studies is becoming increasingly important. In addition, there is a lack of reproducibility of the research results. With the presented open-source architecture, we aim to address these two topics. Therefore, we discuss the advantages and disadvantages of various existing tools from different sub-fields within robotics. Requirements for an architecture can be derived from this overview of the literature, which 1) supports interdisciplinary research, 2) allows reproducibility of the research, and 3) is accessible to other researchers in the field of HRI. With our architecture, we tackle these requirements by providing a Graphical User Interface which explains the robot behavior and allows introspection into the current state of the dialog. Additionally, it offers controlling possibilities to easily conduct Wizard of Oz studies. To achieve transparency, the dialog is modeled explicitly, and the robot behavior can be configured. Furthermore, the modular architecture offers an interface for external features and sensors and is expandable to new robots and modalities.
Keywords: Artificial Intelligence; Computer Science Applications

The data awareness framework as part of data literacies in K-12 education - Höper, Lukas; Schulte, Carsten (Information and Learning Sciences)
In today's digital world, data-driven digital artefacts pose challenges for education, as many students lack an understanding of data and feel powerless when interacting with them. This article addresses these challenges and introduces the data awareness framework. It focuses on understanding data-driven technologies and reflecting on the role of data in everyday life. The paper also presents an empirical study on young school students' data awareness. The study involves a teaching unit on data awareness framed by a pretest-posttest design using a questionnaire on students' awareness and understanding of and reflection on data practices of data-driven digital artefacts. The study's findings indicate that the data awareness framework supports students in understanding data practices of data-driven digital artefacts. The findings also suggest that the framework encourages students to reflect on these data practices and think about their daily behaviour. Students learn a model about interactions with data-driven digital artefacts and use it to analyse data-driven applications. This approach appears to enable students to understand these artefacts from everyday life and reflect on these interactions. The work contributes to research on data and AI literacies and suggests a way to support students in developing self-determination and agency during interactions with data-driven digital artefacts.
Keywords: Library and Information Sciences; Computer Science Applications; Education

Defense-in-Depth als neues Paradigma der sicherheitsgerechten Produktentwicklung: interdisziplinäre, bedrohungsbewusste und lösungsorientierte Security - Gräßler, Iris; Bodden, Eric; Wiechel, Dominik; Pottebaum, Jens (Konstruktion)
inhalt Der verlässliche Betrieb von technischen Produkten wird zunehmend durch bewusste Angriffe bedroht. Vollständige Sicherheit ist dabei nicht möglich, durchschlagende Angriffe sind unvermeidbar (Assume Breach). Dies erfordert einen Paradigmenwechsel in der sicherheitsgerechten Entwicklung mechatronischer und cyber-physischer Systeme hin zu Defense-in-Depth. Systeme müssen so ausgelegt werden, dass sie auch bei gezielten Angriffen möglichst hohe Zuverlässigkeit und Sicherheit gewährleisten. Der hier beschriebene Lösungsansatz erweitert das Systemmodell um Angriffsszenarien und Verteidigungslinien. Diese werden am Beispiel eines industriellen Schließsystems zur Anlagensicherheit erläutert. Entwickler werden sensibilisiert, Angriffe systematisch zu berücksichtigen und interdisziplinär Verteidigungselemente gegenüber Bedrohungen und Angriffen zu spezifizieren.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; Theoretical Computer Science

Investigation of the Compatibility between Warheads and Peptidomimetic Sequences of Protease Inhibitors—A Comprehensive Reactivity and Selectivity Study - Müller, Patrick; Meta, Mergim; Meidner, Jan Laurenz; Schwickert, Marvin; Meyr, Jessica; Schwickert, Kevin; Kersten, Christian; Zimmer, Collin; Hammerschmidt, Stefan Josef; Frey, Ariane; Lahu, Albin; de la Hoz-Rodríguez, Sergio; et al. (International Journal of Molecular Sciences)
Covalent peptidomimetic protease inhibitors have gained a lot of attention in drug development in recent years. They are designed to covalently bind the catalytically active amino acids through electrophilic groups called warheads. Covalent inhibition has an advantage in terms of pharmacodynamic properties but can also bear toxicity risks due to non-selective off-target protein binding. Therefore, the right combination of a reactive warhead with a well-suited peptidomimetic sequence is of great importance. Herein, the selectivities of well-known warheads combined with peptidomimetic sequences suited for five different proteases were investigated, highlighting the impact of both structure parts (warhead and peptidomimetic sequence) for affinity and selectivity. Molecular docking gave insights into the predicted binding modes of the inhibitors inside the binding pockets of the different enzymes. Moreover, the warheads were investigated by NMR and LC-MS reactivity assays against serine/threonine and cysteine nucleophile models, as well as by quantum mechanics simulations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Le Gall, François (SIAM Journal on Computing)
Keywords: General Mathematics; General Computer Science

The Broken Leg of Algorithm Appreciation: An Experimental Study on the Effect of Unobserved Variables on Advice Utilization - Leffrang, Dirk (Wirtschaftsinformatik Conference)
Despite the widespread use of machine learning algorithms, their effectiveness is limited by a phenomenon known as algorithm aversion. Recent research concluded that unobserved variables can cause algorithm aversion. However, the impact of an unobserved variable on algorithm aversion remains unclear. Previous studies focused on situations where humans had more variables available than algorithms. We extend this research by conducting an online experiment with 94 participants, systematically varying the number of observable variables to the advisor and the advisor type. Surprisingly, our results did not confirm that an unobserved variable had a negative effect on advice-taking. Instead, we found a positive impact in an algorithm appreciation scenario. This study provides new insights into the paradoxical behavior in which people weigh advice more despite having fewer variables, as they correct for the advisor's errors. Practitioners should consider this behavior when designing algorithms and account for user correction behavior.
Keywords: Algorithm aversion; Data; Decision-making; Advice-taking; Human-Computer Interaction

Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (Algorithmica)
Abstract Consider a set of jobs connected to a directed acyclic task graph with a fixed source and sink. The edges of this graph model precedence constraints and the jobs have to be scheduled with respect to those. We introduce the server cloud scheduling problem, in which the jobs have to be processed either on a single local machine or on one of infinitely many cloud machines. For each job, processing times both on the server and in the cloud are given. Furthermore, for each edge in the task graph, a communication delay is included in the input and has to be taken into account if one of the two jobs is scheduled on the server and the other in the cloud. The server processes jobs sequentially, whereas the cloud can serve as many as needed in parallel, but induces costs. We consider both makespan and cost minimization. The main results are an FPTAS for the makespan objective for graphs with a constant source and sink dividing cut and strong hardness for the case with unit processing times and delays.
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Rotation r-graphs - Steffen, Eckhard; Wolf, Isaak Hieronymus (Discrete Mathematics)
Keywords: Discrete Mathematics and Combinatorics; Theoretical Computer Science

EEG Correlates of Distractions and Hesitations in Human–Robot Interaction: A LabLinking Pilot Study - Richter, Birte; Putze, Felix; Ivucic, Gabriel; Brandt, Mara; Schütze, Christian; Reisenhofer, Rafael; Wrede, Britta; Schultz, Tanja (Multimodal Technologies and Interaction)
In this paper, we investigate the effect of distractions and hesitations as a scaffolding strategy. Recent research points to the potential beneficial effects of a speaker’s hesitations on the listeners’ comprehension of utterances, although results from studies on this issue indicate that humans do not make strategic use of them. The role of hesitations and their communicative function in human-human interaction is a much-discussed topic in current research. To better understand the underlying cognitive processes, we developed a human–robot interaction (HRI) setup that allows the measurement of the electroencephalogram (EEG) signals of a human participant while interacting with a robot. We thereby address the research question of whether we find effects on single-trial EEG based on the distraction and the corresponding robot’s hesitation scaffolding strategy. To carry out the experiments, we leverage our LabLinking method, which enables interdisciplinary joint research between remote labs. This study could not have been conducted without LabLinking, as the two involved labs needed to combine their individual expertise and equipment to achieve the goal together. The results of our study indicate that the EEG correlates in the distracted condition are different from the baseline condition without distractions. Furthermore, we could differentiate the EEG correlates of distraction with and without a hesitation scaffolding strategy. This proof-of-concept study shows that LabLinking makes it possible to conduct collaborative HRI studies in remote laboratories and lays the first foundation for more in-depth research into robotic scaffolding strategies.
Keywords: Computer Networks and Communications; Computer Science Applications; Human-Computer Interaction; Neuroscience (miscellaneous)

Workarounds as generative mechanisms for bottom‐up process innovation—Insights from a multiple case study - Bartelheimer, Christian; Wolf, Verena; Beverungen, Daniel (Information Systems Journal)
Abstract Workarounds are goal‐driven deviations from the standard operating procedures performed to overcome obstacles constraining day‐to‐day work. Despite starting as temporary fixes, they can become established across an organisation and trigger the innovation of processes and IT artefacts that can resolve misfits permanently. Although prior research has elicited antecedents and types of workarounds, it is not known how workarounds diffuse in an organisation and, thereby, innovating co‐workers' activities, IT artefacts, and organisational structures. The results of our multiple two‐year case study provide unique empirical insights into the diffusion of workarounds and how they can act as generative mechanisms for bottom‐up process innovation.
Keywords: Computer Networks and Communications; Information Systems; Software

Optimal scheduling of a large-scale power-to-ammonia process: Effects of parameter optimization on the indirect demand response potential - Hochhaus, Thorben; Bruns, Bastian; Grünewald, Marcus; Riese, Julia (Computers & Chemical Engineering)
Keywords: Computer Science Applications; General Chemical Engineering

On the Multimodal Resolution of a Search Sequence in Virtual Reality - Klowait, Nils (Human Behavior and Emerging Technologies)
In virtual reality (VR), participants may not always have hands, bodies, eyes, or even voices—using VR helmets and two controllers, participants control an avatar through virtual worlds that do not necessarily obey familiar laws of physics; moreover, the avatar’s bodily characteristics may not neatly match our bodies in the physical world. Despite these limitations and specificities, humans get things done through collaboration and the creative use of the environment. While multiuser interactive VR is attracting greater numbers of participants, there are currently few attempts to analyze the in situ interaction systematically. This paper proposes a video-analytic detail-oriented methodological framework for studying virtual reality interaction. Using multimodal conversation analysis, the paper investigates a nonverbal, embodied, two-person interaction: two players in a survival game strive to gesturally resolve a misunderstanding regarding an in-game mechanic—however, both of their microphones are turned off for the duration of play. The players’ inability to resort to complex language to resolve this issue results in a dense sequence of back-and-forth activity involving gestures, object manipulation, gaze, and body work. Most crucially, timing and modified repetitions of previously produced actions turn out to be the key to overcome both technical and communicative challenges. The paper analyzes these action sequences, demonstrates how they generate intended outcomes, and proposes a vocabulary to speak about these types of interaction more generally. The findings demonstrate the viability of multimodal analysis of VR interaction, shed light on unique challenges of analyzing interaction in virtual reality, and generate broader methodological insights about the study of nonverbal action.
Keywords: Human-Computer Interaction; General Social Sciences; Social Psychology; Virtual Reality : Multimodality; Nonverbal Interaction; Search Sequence; Gesture; Co-Operative Action; Goodwin; Ethnomethodology

Optimization of Rate-Splitting Multiple Access in Beyond Diagonal RIS-assisted URLLC Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard; Clerckx, Bruno (IEEE Transactions on Wireless Communications)
Keywords: Applied Mathematics; Electrical and Electronic Engineering; Computer Science Applications

Spectral and Energy Efficiency Maximization of MISO STAR-RIS-Assisted URLLC Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard A. (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Developing a deep canonical correlation-based technique for seizure prediction - Vieluf, Solveig; Hasija, Tanuj; Kuschel, Maurice; Reinsberger, Claus; Loddenkemper, Tobias (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

An interval multi-criteria decision-making model for evaluating blockchain-IoT technology in supply chain networks - Tavana, Madjid; Khalili Nasr, Arash; Ahmadabadi, Alireza Barati; Amiri, Alireza Shamekhi; Mina, Hassan (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Analytic hierarchy process and data envelopment analysis: A match made in heaven - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

A novel indicator for sustainability in production planning using Center of Gravity-based assessment of Pareto fronts - Hilbert, Markus; Dellnitz, Andreas; Kleine, Andreas; Tavana, Madjid (Computers & Industrial Engineering)
Keywords: General Engineering; General Computer Science

Privacy-centered authentication: A new framework and analysis - Robles-González, Antonio; Arias Cabarcos, Patricia; Parra-Arnau, Javier (Computers & Security)
Keywords: Law; General Computer Science

Visual Interpretability of Image-based Real Estate Appraisal - Kucklick, Jan-Peter (55th Annual Hawaii International Conference on System Sciences (HICSS-55))
Explainability for machine learning gets more and more important in high-stakes decisions like real estate appraisal. While traditional hedonic house pricing models are fed with hard information based on housing attributes, recently also soft information has been incorporated to increase the predictive performance. This soft information can be extracted from image data by complex models like Convolutional Neural Networks (CNNs). However, these are intransparent which excludes their use for high-stakes financial decisions. To overcome this limitation, we examine if a two-stage modeling approach can provide explainability. We combine visual interpretability by Regression Activation Maps (RAM) for the CNN and a linear regression for the overall prediction. Our experiments are based on 62.000 family homes in Philadelphia and the results indicate that the CNN learns aspects related to vegetation and quality aspects of the house from exterior images, improving the predictive accuracy of real estate appraisal by up to 5.4%.
Keywords: Explainable Artificial Intelligence (XAI); Regression Activation Maps; Real Estate Appraisal; Convolutional Block Attention Module; Computer Vision

A Discrete and Continuous Study of the Max-Chain-Formation Problem - Castenow, Jannik; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Information and Computation)
Keywords: Computational Theory and Mathematics; Computer Science Applications; Information Systems; Theoretical Computer Science

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Computation on Encrypted Data Using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kußmaul, Jörn; Janneck, Jonas; Kerschbaum, Florian; Bodden, Eric (ACM Transactions on Privacy and Security)
Encrypting data before sending it to the cloud ensures data confidentiality but requires the cloud to compute on encrypted data. Trusted execution environments, such as Intel SGX enclaves, promise to provide a secure environment in which data can be decrypted and then processed. However, vulnerabilities in the executed program give attackers ample opportunities to execute arbitrary code inside the enclave. This code can modify the dataflow of the program and leak secrets via SGX side channels. Fully homomorphic encryption would be an alternative to compute on encrypted data without data leaks. However, due to its high computational complexity, its applicability to general-purpose computing remains limited. Researchers have made several proposals for transforming programs to perform encrypted computations on less powerful encryption schemes. Yet current approaches do not support programs making control-flow decisions based on encrypted data. We introduce the concept of dataflow authentication (DFAuth) to enable such programs. DFAuth prevents an adversary from arbitrarily deviating from the dataflow of a program. Our technique hence offers protections against the side-channel attacks described previously. We implemented two flavors of DFAuth, a Java bytecode-to-bytecode compiler, and an SGX enclave running a small and program-independent trusted code base. We applied DFAuth to a neural network performing machine learning on sensitive medical data and a smart charging scheduler for electric vehicles. Our transformation yields a neural network with encrypted weights, which can be evaluated on encrypted inputs in \( 12.55 \,ms \) . Our protected scheduler is capable of updating the encrypted charging plan in approximately 1.06 seconds.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate - Hanke, Marcel; Hansen, Niklas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation time. Using DNA origami nanostructures as sensors that translate small molecular transitions into nanostructural changes, the denaturing effects of the Gdm salts were directly visualized by atomic force microscopy. GdmSCN was the most potent DNA denaturant, which caused complete DNA origami denaturation at 50 °C already at a concentration of 2 M. Under such harsh conditions, denaturation occurred within the first 15 min of Gdm exposure, whereas much slower kinetics were observed for the more weakly denaturing salt Gdm2SO4 at 25 °C. Lastly, we observed a novel non-monotonous temperature dependence of DNA origami denaturation in Gdm2SO4 with the fraction of intact nanostructures having an intermediate minimum at about 40 °C. Our results, thus, provide further insights into the highly complex Gdm–DNA interaction and underscore the importance of the counteranion species.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Joining of CFRT/Steel Hybrid Parts via Direct Pressing of Cold Formed Non-Rotational Symmetric Pin Structures - Popp, Julian; Römisch, David; Merklein, Marion; Drummer, Dietmar (Applied Sciences)
In this study, quasi-unidirectional continuous fiber reinforced thermoplastics (CFRTs) are joined with metal sheets via cold formed cylindrical, elliptical and polygonal pin structures which are directly pressed into the CFRT component after local infrared heating. In comparison to already available studies, the unique novelty is the use of non-rotational symmetric pin structures for the CFRT/metal hybrid joining. Thus, a variation in the fiber orientation in the CFRT component as well as a variation in the non-rotational symmetric pins’ orientation in relation to the sample orientation is conducted. The created samples are consequently mechanically tested via single lap shear experiments in a quasi-static state. Finally, the failure behavior of the single lap shear samples is investigated with the help of microscopic images and detailed photographs. In the single lap shear tests, it could be shown that non-rotational symmetric pin structures lead to an increase in maximum testing forces of up to 74% when compared to cylindrical pins. However, when normalized to the pin foot print related joint strength, only one polygonal pin variation showed increased joint strength in comparison to cylindrical pin structures. The investigation of the failure behavior showed two distinct failure modes. The first failure mode was failure of the CFRT component due to an exceedance of the maximum bearing strength of the pin-hole leading to significant damage in the CFRT component. The second failure mode was pin-deflection due to the applied testing load and a subsequent pin extraction from the CFRT component resulting in significantly less visible damage in the CFRT component. Generally, CFRT failure is more likely with a fiber orientation of 0° in relation to the load direction while pin extraction typically occurs with a fiber orientation of 90°. It is assumed that for future investigations, pin structures with an undercutting shape that creates an interlocking joint could counteract the tendency for pin-extraction and consequently lead to increased maximum joint strengths.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Mincut Sensitivity Data Structures for the Insertion of an Edge - Baswana, Surender; Gupta, Shiv; Knollmann, Till (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Anion-specific structure and stability of guanidinium-bound DNA origami - Hanke, Marcel; Dornbusch, Daniel; Hadlich, Christoph; Rossberg, Andre; Hansen, Niklas; Grundmeier, Guido; Tsushima, Satoru; Keller, Adrian; Fahmy, Karim (Computational and Structural Biotechnology Journal)
Keywords: Computer Science Applications; Genetics; Biochemistry; Structural Biology; Biophysics; Biotechnology

Robust estimation of clinch joint characteristics based on data-driven methods - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (The International Journal of Advanced Manufacturing Technology)
Given a steadily increasing demand on multi-material lightweight designs, fast and cost-efficient production technologies, such as the mechanical joining process clinching, are becoming more and more relevant for series production. Since the application of such joining techniques often base on the ability to reach similar or even better joint loading capacities compared to established joining processes (e.g., spot welding), few contributions investigated the systematic improvement of clinch joint characteristics. In this regard, the use of data-driven methods in combination with optimization algorithms showed already high potentials for the analysis of individual joints and the definition of optimal tool configurations. However, the often missing consideration of uncertainties, such as varying material properties, and the related calculation of their impact on clinch joint properties can lead to poor estimation results and thus to a decreased reliability of the entire joint connection. This can cause major challenges, especially for the design and dimensioning of safety-relevant components, such as in car bodies. Motivated by this, the presented contribution introduces a novel method for the robust estimation of clinch joint characteristics including uncertainties of varying and versatile process chains in mechanical joining. Therefore, the utilization of Gaussian process regression models is demonstrated and evaluated regarding the ability to achieve sufficient prediction qualities.
Keywords: Industrial and Manufacturing Engineering; Computer Science Applications; Mechanical Engineering; Software; Control and Systems Engineering

Seizing the Opportunity for Automation—How Traffic Density Determines Truck Drivers' Use of Cruise Control - Hoffmann, Christin; Thommes, Kirsten (IEEE Transactions on Human-Machine Systems)
Keywords: Artificial Intelligence; Computer Networks and Communications; Computer Science Applications; Human-Computer Interaction; Signal Processing; Control and Systems Engineering; Human Factors and Ergonomics

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Learning to Plan by Learning to Reflect?—Exploring Relations between Professional Knowledge, Reflection Skills, and Planning Skills of Preservice Physics Teachers in a One-Semester Field Experience - Vogelsang, Christoph; Kulgemeyer, Christoph; Riese, Josef (Education Sciences)
Following concepts describing lesson planning as a form of anticipatory reflection, preservice physics teachers’ reflection skills are assumed to be positively connected with their planning skills. However, empirical evidence on this is scarce. To explore how relations between these specific skills change over the course of a field experience controlling for influences of professional knowledge, we conduct a pre-post field study with N = 95 preservice physics teachers in a one-semester field experience. Content knowledge (CK) and pedagogical content knowledge (PCK) (paper-and-pencil tests), and reflection and planning skills (standardized performance assessments) were assessed before and after the field experience. Path analyses revealed almost no influence of reflection skills on planning skills. Reflections skills did not contribute to preservice teachers planning skills beyond knowledge, indicating both constructs might represent rather independent abilities. The results show the need for further development of models describing the development of teachers’ professional knowledge and skills in academic teacher education and for the development of concepts for a better integration of reflection and lesson planning in field experiences.
Keywords: Public Administration; Developmental and Educational Psychology; Education; Computer Science Applications; Computer Science (miscellaneous); Physical Therapy; Sports Therapy and Rehabilitation

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
Abstract While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Abnormal geodesics in 2D-Zermelo navigation problems in the case of revolution and the fan shape of the small time balls - Bonnard, B.; Cots, O.; Gergaud, J.; Wembe Moafo, Boris Edgar (Systems & Control Letters)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; General Computer Science; Control and Systems Engineering

Applying XAI to an AI-based system for candidate management to mitigate bias and discrimination in hiring - Hofeditz, Lennart; Clausen, Sünje; Rieß, Alexander; Mirbabaie, Milad; Stieglitz, Stefan (Electronic Markets (ELMA))
Abstract Assuming that potential biases of Artificial Intelligence (AI)-based systems can be identified and controlled for (e.g., by providing high quality training data), employing such systems to augment human resource (HR)-decision makers in candidate selection provides an opportunity to make selection processes more objective. However, as the final hiring decision is likely to remain with humans, prevalent human biases could still cause discrimination. This work investigates the impact of an AI-based system’s candidate recommendations on humans’ hiring decisions and how this relation could be moderated by an Explainable AI (XAI) approach. We used a self-developed platform and conducted an online experiment with 194 participants. Our quantitative and qualitative findings suggest that the recommendations of an AI-based system can reduce discrimination against older and female candidates but appear to cause fewer selections of foreign-race candidates. Contrary to our expectations, the same XAI approach moderated these effects differently depending on the context.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

The Investigator’s Dilemma - A Review of Social Media Analytics Research Ethics in Information Systems - Marx, Julian; Mirbabaie, Milad (Australasian Journal of Information Systems)
Social media have become not only integral parts of our private and professional lives, but also an indispensable source of data for empirical research across a variety of academic disciplines. Applying a Social Media Analytics (SMA) methodology, however, imposes heavy ethical challenges on researchers. Scholars in the Information Systems (IS) discipline must deal with a patchwork of ethical frameworks, regulations, and (missing) institutional support. To initiate a debate on how to develop a common understanding of SMA research ethics, this paper compiles a scoping review of extant literature and suggests a research agenda for IS scholarship on this matter. The review yields a total of eight fundamental principles of ethical SMA research, which provide a starting point to guiding individual researchers towards more ethical conduct. At the same time, this work unearths a multitude of intricate dilemmas that are currently unresolved. The findings of this review will encourage IS scholarship to find its own voice in the debate about social media research ethics.
Keywords: Information Systems and Management; Human-Computer Interaction; Business; Management and Accounting (miscellaneous); Information Systems

How crises are different - Design principles for conversational agents to support Emergency Management Agencies - Stieglitz, Stefan; Hofeditz, Lennart; Brünker, Felix; Ehnis, Christian; Mirbabaie, Milad; Ross, Björn (International Journal of Information Management)
Keywords: Library and Information Sciences; Computer Networks and Communications; Information Systems

Toward a Competence Model for Graphical Modeling - Soyka, Chantal; Schaper, Niclas; Bender, Elena; Striewe, Michael; Ullrich, Meike (ACM Transactions on Computing Education)
Modeling is an integral part of many computing-related disciplines and thus also represents a curricular core component in computing education in tertiary education. Competence models in which modeling is integrated at least to some extent already exist in some of these disciplines. However, for the core component of graphical modeling, a competence model that illuminates the relevant competences in detail is still lacking. Therefore, we develop a competence model for graphical modeling with the aim to make teaching and especially assessments in the field more competence-oriented. This paper reports on the first two studies conducted to develop and validate the competence model for graphical modeling. In the first study, the structure of the competence model was developed based on theories and approaches of educational science. Competences relevant for graphical modeling were deductively derived from literature and existing university course descriptions using techniques of qualitative content analysis. The result of the first study is a preliminary competence model. In the second study, the preliminary competence model was reviewed by means of an expert rating in the modeling community. The competence model was revised and refined based on these findings and subsequent expert discussions. The main result of the investigation represents the competence model for graphical modeling (CMGM), which includes a total of 74 competence facets at different cognitive process levels in the five content areas of ”model understanding and interpreting”, ”model building and modifying”, ”values, attitudes, and beliefs”, ”metacognitive knowledge and skills”, and ”social-communicative skills”.
Keywords: graphical modeling; conceptual modeling; computer science; competence model; higher education

Stating Comparison Score Uncertainty and Verification Decision Confidence Towards Transparent Face Recognition - Huber, Marco; Terhörst, Philipp; Kirchbuchner, Florian; Damer, Naser; Kuijper, Arjan (33nd British Machine Vision Conference 2022)
Keywords: Computer Vision and Pattern Recognition (cs.CV); FOS: Computer and information sciences; FOS: Computer and information sciences

Physics informed neural networks for continuum micromechanics - Henkes, Alexander; Wessels, Henning; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Social/dialogical roles of social robots in supporting children’s learning of language and literacy—A review and analysis of innovative roles - Rohlfing, Katharina; Altvater-Mackensen, Nicole; Caruana, Nathan; van den Berghe, Rianne; Bruno, Barbara; Tolksdorf, Nils Frederik; Hanulíková, Adriana (Frontiers in Robotics and AI)
One of the many purposes for which social robots are designed is education, and there have been many attempts to systematize their potential in this field. What these attempts have in common is the recognition that learning can be supported in a variety of ways because a learner can be engaged in different activities that foster learning. Up to now, three roles have been proposed when designing these activities for robots: as a teacher or tutor, a learning peer, or a novice. Current research proposes that deciding in favor of one role over another depends on the content or preferred pedagogical form. However, the design of activities changes not only the content of learning, but also the nature of a human–robot social relationship. This is particularly important in language acquisition, which has been recognized as a social endeavor. The following review aims to specify the differences in human–robot social relationships when children learn language through interacting with a social robot. After proposing categories for comparing these different relationships, we review established and more specific, innovative roles that a robot can play in language-learning scenarios. This follows Mead’s (1946) theoretical approach proposing that social roles are performed in interactive acts. These acts are crucial for learning, because not only can they shape the social environment of learning but also engage the learner to different degrees. We specify the degree of engagement by referring to Chi’s (2009) progression of learning activities that range from active, constructive, toward interactive with the latter fostering deeper learning. Taken together, this approach enables us to compare and evaluate different human–robot social relationships that arise when applying a robot in a particular social role.
Keywords: Artificial Intelligence; Computer Science Applications

Two-Colour Spectrally Multimode Integrated SU(1,1) Interferometer - Ferreri, Alessandro; Sharapova, Polina R. (Symmetry)
Multimode integrated interferometers have great potential for both spectral engineering and metrological applications. However, the material dispersion of integrated platforms constitutes an obstacle that limits the performance and precision of such interferometers. At the same time, two-colour nonlinear interferometers present an important tool for metrological applications, when measurements in a certain frequency range are difficult. In this manuscript, we theoretically developed and investigated an integrated multimode two-colour SU(1,1) interferometer operating in a supersensitive mode. By ensuring the proper design of the integrated platform, we suppressed the dispersion, thereby significantly increasing the visibility of the interference pattern. The use of a continuous wave pump laser provided the symmetry between the spectral shapes of the signal and idler photons concerning half the pump frequency, despite different photon colours. We demonstrate that such an interferometer overcomes the classical phase sensitivity limit for wide parametric gain ranges, when up to 3×104 photons are generated.
Keywords: Physics and Astronomy (miscellaneous); General Mathematics; Chemistry (miscellaneous); Computer Science (miscellaneous)

Quantum generalizations of the polynomial hierarchy with applications to QMA(2) - Gharibian, Sevag; Santha, Miklos; Sikora, Jamie; Sundaram, Aarthi; Yirka, Justin (Computational Complexity)
Keywords: Computational Mathematics; Computational Theory and Mathematics; General Mathematics; Theoretical Computer Science

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

NTFA-enabled goal-oriented adaptive space–time finite elements for micro-heterogeneous elastoplasticity problems - Ju, X.; Mahnken, Rolf; Xu, Y.; Liang, L. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

New low order Runge–Kutta schemes for asymptotically exact global error estimation of embedded methods without order reduction - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Proactive Management of Requirement Changes in the Development of Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Preuß, Daniel (Applied Sciences)
Requirement changes and cascading effects of change propagation are major sources of inefficiencies in product development and increase the risk of project failure. Proactive change management of requirement changes yields the potential to handle such changes efficiently. A systematic approach is required for proactive change management to assess and reduce the risk of a requirement change with appropriate effort in industrial application. Within the paper at hand, a novel method for Proactive Management of Requirement Changes (ProMaRC) is presented. It is developed in close collaboration with industry experts and evaluated based on workshops, pilot users’ feedback, three industrial case studies from the automotive industry and five development projects from research. To limit the application effort, an automated approach for dependency analysis based on the machine learning technique BERT and semi-automated assessment of change likelihood and impact using a modified PageRank algorithm is developed. Applying the method, the risks of requirement changes are assessed systematically and reduced by means of proactive change measures. Evaluation shows high performance of dependency analysis and confirms the applicability and usefulness of the method. This contribution opens up the research space of proactive risk management for requirement changes which is currently almost unexploited. It enables more efficient product development.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Even Factors in Edge-Chromatic-Critical Graphs with a Small Number of Divalent Vertices - Steffen, Eckhard; Wolf, Isaak Hieronymus (Graphs and Combinatorics)
Keywords: Discrete Mathematics and Combinatorics; Theoretical Computer Science

A parameterized view on the complexity of dependence and independence logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Journal of Logic and Computation)
Abstract In this paper, we investigate the parameterized complexity of model checking for Dependence and Independence logic, which are well studied logics in the area of Team Semantics. We start with a list of nine immediate parameterizations for this problem, namely the number of disjunctions (i.e. splits)/(free) variables/universal quantifiers, formula-size, the tree-width of the Gaifman graph of the input structure, the size of the universe/team and the arity of dependence atoms. We present a comprehensive picture of the parameterized complexity of model checking and obtain a division of the problem into tractable and various intractable degrees. Furthermore, we also consider the complexity of the most important variants (data and expression complexity) of the model checking problem by fixing parts of the input.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

Towards electronic structure-based ab-initio molecular dynamics simulations with hundreds of millions of atoms - Schade, Robert; Kenter, Tobias; Elgabarty, Hossam; Lass, Michael; Schütt, Ole; Lazzaro, Alfio; Pabst, Hans; Mohr, Stephan; Hutter, Jürg; Kühne, Thomas; Plessl, Christian (Parallel Computing)
Keywords: Artificial Intelligence; Computer Graphics and Computer-Aided Design; Computer Networks and Communications; Hardware and Architecture; Theoretical Computer Science; Software

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia A.; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Banking the Future of Banking: Savings banks and the Digital Age in East and West Germany - Schmitt, Martin (Prophets of Computing: Visions of Society Transformed by Computing)
Keywords: Sparkassen; Computer; 1960er; Kreditwirtschaft; Digitalisierung; Deutschland {<}DDR{>}; Deutschland {<}Bundesrepublik{>}

Demand response scheduling using derivative-based dynamic surrogate models - Di Pretoro, Alessandro; Bruns, Bastian; Negny, Stéphane; Grünewald, Marcus; Riese, Julia (Computers & Chemical Engineering)
Keywords: Computer Science Applications; General Chemical Engineering

Rate Splitting in MIMO RIS-Assisted Systems With Hardware Impairments and Improper Signaling - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard A. (IEEE Transactions on Vehicular Technology)
Keywords: Electrical and Electronic Engineering; Computer Networks and Communications; Aerospace Engineering; Automotive Engineering

Improper Signaling for Multicell MIMO RIS-Assisted Broadcast Channels With I/Q Imbalance - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J. (IEEE Transactions on Green Communications and Networking)
Keywords: Computer Networks and Communications; Renewable Energy; Sustainability and the Environment

A novel Interval Type-2 Fuzzy best-worst method and combined compromise solution for evaluating eco-friendly packaging alternatives - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Bonyani, Abbas (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

Exploiting Hardware-Based Data-Parallel and Multithreading Models for Smart Edge Computing in Reconfigurable FPGAs - Rodriguez, Alfonso; Otero, Andres; Platzner, Marco; De la Torre, Eduardo (IEEE Transactions on Computers)
Keywords: Computational Theory and Mathematics; Hardware and Architecture; Theoretical Computer Science; Software

Nowhere-zero 3-flows in toroidal graphs - Li, Jiaao; Ma, Yulai; Miao, Zhengke; Shi, Yongtang; Wang, Weifan; Zhang, Cun-Quan (Journal of Combinatorial Theory, Series B)
Keywords: Computational Theory and Mathematics; Discrete Mathematics and Combinatorics; Theoretical Computer Science

An automated approach for developing neural network interatomic potentials with FLAME - Mirhosseini, Hossein; Tahmasbi, Hossein; Kuchana, Sai Ram; Ghasemi, Alireza; Kühne, Thomas (Computational Materials Science)
Keywords: Computational Mathematics; General Physics and Astronomy; Mechanics of Materials; General Materials Science; General Chemistry; General Computer Science

Fast Hands-Off Control Using ADMM Real-Time Iterations - Schulze Darup, Moritz; Book, Gerrit; Quevedo, Daniel E.; Nagahara, Masaaki (IEEE Transactions on Automatic Control)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

On the Stability of Linear Dynamic Controllers With Integer Coefficients - Schluter, Nils; Darup, Moritz Schulze (IEEE Transactions on Automatic Control)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Collaborating with Virtual Assistants in Organizations: Analyzing Social Loafing Tendencies and Responsibility Attribution - Stieglitz, Stefan; Mirbabaie, Milad; Möllmann, Nicholas R. J.; Rzyski, Jannik (Information Systems Frontiers)
Abstract Organizations increasingly introduce collaborative technologies in form of virtual assistants (VAs) to save valuable resources, especially when employees are assisted with work-related tasks. However, the effect of VAs on virtual teams and collaboration remains uncertain, particularly whether employees show social loafing (SL) tendencies, i.e., applying less effort for collective tasks compared to working alone. While extant research indicates that VAs collaboratively working in teams exert greater results, less is known about SL in virtual collaboration and how responsibility attribution alters. An online experiment with N = 102 was conducted in which participants were assisted by a VA in solving a task. The results indicate SL tendencies in virtual collaboration with VAs and that participants tend to cede responsibility to the VA. This study makes a first foray and extends the information systems (IS) literature by analyzing SL and responsibility attribution thus updates our knowledge on virtual collaboration with VAs.
Keywords: Computer Networks and Communications; Information Systems; Theoretical Computer Science; Software

The rise of artificial intelligence – understanding the AI identity threat at the workplace - Mirbabaie, Milad; Brünker, Felix; Möllmann Frick, Nicholas R. J.; Stieglitz, Stefan (Electronic Markets)
Abstract Artificial intelligence (AI) is being increasingly integrated into enterprises to foster collaboration within humanmachine teams and assist employees with work-related tasks. However, introducing AI may negatively impact employees’ identifications with their jobs as AI is expected to fundamentally change workplaces and professions, feeding into individuals’ fears of being replaced. To broaden the understanding of the AI identity threat, the findings of this study reveal three central predictors for AI identity threat in the workplace: changes to work, loss of status position, and AI identity predicting AI identity threat in the workplace. This study enriches information systems literature by extending our understanding of collaboration with AI in the workplace to drive future research in this field. Researchers and practitioners understand the implications of employees’ identity when collaborating with AI and comprehend which factors are relevant when introducing AI in the workplace.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Digitally Assessing Text Comprehension in Grades 3-4: Test Development and Validation - Seifert, Susanne; Paleczek, Lisa (Electronic Journal of e-Learning)
A prerequisite for child reading support at school is adequate assessment. Embedding (repeated) assessment into daily teaching routine is often challenging for teachers in terms of time and organization. The use of digital tools can help teachers in the assessment process (in preparation, evaluation, documentation, etc.). A digital assessment tool (Graz Reading Comprehension test: GraLeV), focusing on assessing reading comprehension skills in Grades 3 and 4 is currently being developed in Austria. This reading assessment covers reading comprehension at the word, sentence, and text level. Text level is assessed via two subtests (Subtest I: presentation of nonsense-stories and corresponding questions, and Subtest II: maze selection). The other levels consist of one subtest each. This paper focusses on the subtests at text level. More specifically, the paper reports the results of two studies. Study 1 describes the development phases and the first piloting of these two subtests (data collection: 10/2019-12/2019). Testing 273 students with preliminary versions of the subtests (Subtest I: 30 items, Subtest II: 60 items) produced information on (a) item difficulty, (b) item discriminatory power, and (c) time limits for future speed testing. Items not meeting the required quality criteria were excluded. The final version of Subtest I consists of 16 questions referring to eight different, short, nonsense-texts. Its testing time (without instructions) is three minutes. The final version of the Subtest II consists of 2 texts each with 15 maze selections (30 items) and testing time is 100 seconds. The internal consistency is found to be good for Subtest I (α=.87) and Subtest II (α=.78 to .80). Study 2 reports on testing for validity and retest-reliability (data collection: 09/2020-11/2020). Student scores in another reading comprehension test, together with teacher assessments of reading comprehension, were used to assess congruent validity. Divergent validity was assessed using teacher assessments of mathematical and socio-emotional skills. As expected, the correlations with the congruent measures were higher than those with the divergent measures. A subsample was tested twice with the GraLeV. Retest-reliability was acceptable for Subtest II. However, the scores obtained at time 2 were higher compared to those at time 1 in both subtests. This is probably the result of increased student familiarity with the digital device and the digital test environment at time 2. The results are discussed in the light of teachers’ needs for standardized digital assessments in order to facilitate the tailoring of student reading support.
Keywords: Computer Science Applications; Education

Is Reading Comprehension Taken for Granted? An Analysis of Austrian Textbooks in Fourth and Sixth Grade - Seifert, Susanne (Technology, Knowledge and Learning)
Abstract The range of teaching materials now available is becoming increasingly diverse. Despite this, however, the use and influence of textbooks in teaching still remains very high. When instructing reading comprehension, teachers often use textbooks as the basis for teaching in language lessons. Establishing a good match between textbooks and the skills to be acquired is therefore essential. In this paper, I investigate whether textbooks used in Austrian schools can adequately support the teaching of reading comprehension skills. Since reading comprehension is the basis for acquiring knowledge in all subjects, science textbooks are examined in addition to (German) language lesson textbooks. Thus, the content pages of four language textbooks and four science textbooks for fourth and sixth grade were analysed in terms of five different categories, i.e. general structural setup, learning goals, text types, text structures, and activities. The results reveal clear variations with respect to learning goals in language textbooks. For example, the extent to which reading comprehension is addressed ranges from 13.64 to 69.70%, depending on the book used. Although not addressed as a learning goal in the science textbooks, reading comprehension is often presupposed, especially in sixth grade. While the instruction of reading comprehension ought to entail coverage of reading strategies, this is often neglected, or only dealt with indirectly. Given the diversity of textbooks analysed, it seems all the more important to stress that teachers should: 1) clarify the goals and teaching strategies of a book before using it, 2) become aware of strategies that support the development of students' reading comprehension, and 3) use textbooks as a complementary (and not sole) tool to support reading comprehension in all subjects.
Keywords: Computer Science Applications; Human-Computer Interaction; Education; Mathematics (miscellaneous)

I-AID: Identifying Actionable Information From Disaster-Related Tweets - Zahera, H.M.A; Jalota, Rricha; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science